The Application of Islamic Values in Decision-Making and Organizational Work Culture: (A Case Study in the Papkis Division of the Regional Office of the Ministry of Religious Affairs in South Kalimantan Province) - Muhammad Ridho; Muhammad Agus Salim; Rochmatunnisa; Norwinda (JIS: Journal Islamic Studies, 2026)
This study provides an in-depth and comprehensive examination and analysis of the integration of Islamic values and their significant role in decision-making processes and the work environment within organizations engaged in Islamic Religious Education and Religious Education (PAPKIS) at the Regional Office of the Ministry of Religious Affairs in South Kalimantan Province. The rationale behind this study is the importance of integrating Islamic principles, such as consultation (musyawarah), trustworthiness (amanah), justice, and duty, into the governance of government organizations, particularly those with religious functions. The objective of this study is to understand how Islamic values are applied in the decision-making process by leaders and their impact on employee work culture. This study adopts a descriptive qualitative research method. Data sources consist of primary data collected through observation and interviews with division heads, team leaders, and external informants (partners) in the PAPKIS division of the Regional Office of the Ministry of Religious Affairs of South Kalimantan Province, while secondary data was obtained through documentary data in the form of policy documents, meeting minutes, and standard operating procedures. The instruments for data collection included observation guides, interviews, and document review. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The findings of the study indicate that Islamic principles have been consistently applied in decision-making processes and workplace culture, thereby fostering a professional and harmonious work environment focused on public service with integrity.